2009
DOI: 10.1038/mp.2008.148
|View full text |Cite
|
Sign up to set email alerts
|

A SNAP25 promoter variant is associated with early-onset bipolar disorder and a high expression level in brain

Abstract: Bipolar disorder (BD) is one of the most common and persistent psychiatric disorders. Earlyonset BD has been shown to be the most severe and familial form. We recently carried out a whole-genome linkage analysis on sibpairs affected by early-onset BD and showed that the 20p12 region was more frequently shared in our families than expected by chance. The synaptosomal-associated protein SNAP25 is a presynaptic plasma membrane protein essential for the triggering of vesicular fusion and neurotransmitter release, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 47 publications
3
57
0
1
Order By: Relevance
“…Our results for the 20p12 region are consistent with several studies (McInnis et al, 2003;Fallin et al, 2004;Jones et al, 2007;Etain et al, 2009). By contrast, the 7q36 region has been reported in only two scans (Jones et al, 2007;Cassidy et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Our results for the 20p12 region are consistent with several studies (McInnis et al, 2003;Fallin et al, 2004;Jones et al, 2007;Etain et al, 2009). By contrast, the 7q36 region has been reported in only two scans (Jones et al, 2007;Cassidy et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we demonstrated that chronic MPH treatment reduces SNAP-25 immunocontent in hippocampus of juvenile rats. Dysfunction of SNAP-25 is linked to various human mental disorders, such as ADHD, schizophrenia, and early-onset bipolar disorder [57][58][59]. Based on this, our result could compromise cell events such as exocytosis, neurite outgrowth, neuronal development, as well as hormone and neurotransmitter release.…”
Section: Discussionmentioning
confidence: 69%
“…In neurons, SNAP25 is located at the presynaptic plasma membrane where it also modulates the activity of voltage-gated calcium channels [8,39,58]. Polymorphisms in SNAP25 have been associated with different neuropsychiatric conditions such as ADHD (reviewed in [9]), schizophrenia, bipolar disorders, and autism [9,13,23], and variants in the gene were reported to modulate cognitive performances [19,20,45]. In particular, SNPs located in a *14 kb region in intron 1 were associated with the intelligence quotient (IQ) in Dutch cohorts [19,20].…”
Section: Introductionmentioning
confidence: 99%